Using pH value to control intermolecular electronic decay - Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (Angewandte Chemie. International edition, 2011)
pH deed: Intermolecular Coulombic decay (ICD) is an ultrafast relaxation pathway of a highly excited system. A theoretical investigation of ammonia dimers and trimers shows that the ICD efficiency is regulated by protonation or deprotonation. Varying the ICD rate by changing the environmental pH value provides a control over the relaxation dynamics (see scheme).
Gesehen am 11.07.2022